The relevancy of outdoor classroom for PBL approach in selected university in Kuala Lumpur - Mohd. Yaman, Maheran; Abdullah, Fadzidah; Rozali, Nur Fadhilah; Salim, Farha (Malaysian Institute of Planners, 2018)
Outdoor classroom could be described as outdoor learning space that provides varying experiences and learning activities that could enhance students’ learning performances, particularly in Problem Based Learning (PBL) approach. It also has become the main role in providing effective and dynamic learning environment for PBL practices. By investigating the relationship between the outdoor classroom and the students’ PBL approach, one could reveal the interconnectedness between the outdoor classrooms in campus settings with the students’ learning performances in PBL approach. Hence, the objective of this study is to analyze the relevance of outdoor classroom in adapting PBL approach in selected universities in Malaysia. A questionnaire survey, was conducted among landscape architecture and architecture students in UIAM, UPM and UiTM Puncak Alam. The results of this study confirm that outdoor classroom improves students learning performances, particularly in designing skills and work presentations. Furthermore, the results also indicate that outdoor classroom enhance students’ ideas and inspiration in designing.